Formulation and Physical Test of Ethanolic Extract Sambiloto Leaves (Andrographis paniculata) Ointment - Dewi, Indri Kusuma; Lestari, Titik; Rofi'ah, Siti Nur (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2015)
Introduction: Andrographis paniculata had known contained active substance such as andrographolida, atsiri oil, flavonoid, tannin, alkaloid, and saponin which functions as antibacterial, antitoxic, analgesic, and anti-pyretic. Based on its antibacterial properties, an ointment form of Andrographis paniculata leaf is then formulated, for practical usage. Ointment formula is semi solid for topical use in the skin or mucosal membranes. Objectives: to know the result of ointment physical test of etanolic extract Andrographis paniculata leaf. Methods: physical tests contain organoleptic test, pH, homogenity, adhesion test and dispersive test. Results: Ointment shaped semi solid, blacky green and special smell of Andrographis paniculata, pH 6, homogenity test obtained homogenous results, adhesion test was 82 second and dispersive test was 5.6 cm. Conclusion: the result of physical tests of etanolic Andrographis paniculata leaf extract ointment appropriate with quality standard.